Modelling the temperature and pH decline early post-mortem of beef carcasses - Xavier, Cristina (2014)
The objective of this work was to model the pH and temperature decline early post-mortem on beef carcasses and to study the effect of gender, genotype and weight class on the pH and temperature decline patterns. A total of 24 beef animals slaughtered in a local abattoir were sampled. pH and temperature were recorded using an OMEGA wireless receiver/host (UWTC-RECl). The decline of pH and temperature was modelled using one parameterisation of the exponential decay function, and its parameters were estimated using the software R. The fitted models were used to predict p H and temperature at 1.5 h, at 3.0 h and at 24 h; the time when p H reached 6.0, and the temperature at which p H reached 6.0. The rate parameters of the exponential decay function for pH (KpH) and temperature (KT) were found to be independent (r=0.35, P>0.05). The correlation between p H at 3 h and final p H (at 24 h) was very high (r=0.930, P<0.01). The KT was influenced by the time elapsed from slaughter until the first recording, and by the carcass weight. In opposition, those variables did not affect the KpH, The exponential decay function was able to model the early post-mortem decline of both p H and temperature, and the pII at 3 hours can be used as predictor of the final pH of beef meat.